2019
DOI: 10.4314/jasem.v23i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and antioxidant evaluation of lemon grass (<i>Cymbopogon citratus</i> DC.) Stapf leaves

Abstract: Cymbopogon citratus commonly called lemon grass is claimed to possess diverse medicinal value among different cultures. The present study determined the phytochemicals and evaluated the antioxidant potential of Cymbopogon citratus leaves. The phytochemical and proximate analysis of the powdered leaves were carried out using standard methods. The antioxidant activity of the crude methanol extract and its fractions (n-hexane, ethyl acetate and chloroform) was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 13 publications
(11 reference statements)
2
17
0
Order By: Relevance
“…Also, concentration-dependent scavenging activity of EOCC against FRAP radicals was observed. In line with findings by Unuigbe et al (2019), our results suggest that EOCC is an excellent antioxidant agent and may guard against oxidative stress by sequestering Iron II ions.…”
Section: In Vitro Antioxidant Activities Of Eoccsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, concentration-dependent scavenging activity of EOCC against FRAP radicals was observed. In line with findings by Unuigbe et al (2019), our results suggest that EOCC is an excellent antioxidant agent and may guard against oxidative stress by sequestering Iron II ions.…”
Section: In Vitro Antioxidant Activities Of Eoccsupporting
confidence: 91%
“…Boukhatem et al, 2014;Garcia et al, 2015); the anti-nociceptive action (Quintans-Junior et al 2011) and in vitro immunomodulatory effects of citral one of its major constituent (Bachiega & Sforcin, 2011). These studies have shown that the leaves of C. citratus contain important phytotherapeutic compounds that confer the antioxidant, anti-inflammatory, (Unuigbe et al, 2019), anxiolytic (Costa et al, 2011), anti-fungi, anti-bacteria, anti-mutagenicity, anti-obesity (Olorunnisola et al, 2014), anti-malaria (Chukwuocha et al, 2016) properties of the plant. Also, several reviews on C. citratus discuss its anti-algesic, anti-hermetic, antispasmodic, antidyspeptic, anti-fever effects, antiseptic, antipyretic, tranquillizing, and diuretic potentials (Ademuyiwa et al, 2015;Oladeji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Phenols: About 2 mL of fungal extract was taken and mixed with aqueous 5% FeCl3 and observed for deep blue or black color formation [39].…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…Anthraquinone is beneficial in hampering the growth of cancer through certain activities such as inducing apoptosis and reliving bowl movements [32]. Antioxidant ability of plant phenolic compound has been attributed to the presence of hydroxyl substituents and their aromatic structure, which enables them to scavenge free radicals [33]. Flavonoid content ranged from (0.40mg/g-2.24mg/g)in dried lemon grass (DL), and raw P. amarus leaf.…”
Section: Phytochemical Composition Of Phyllantus Amarus and Cymbopogan Citratusmentioning
confidence: 99%